Growth and yield attributes of cowpea accessions grown under different soil amendments in a derived Savannah zone - Agatha Ifeoma Atugwu; Uchechukwu Paschal Chukwudi; Emmanuel Ikechukwu Eze; Maureen Ogonna Ugwu; Jacob Ikechukwu Enyi (AIMS Agriculture and Food, 2023)
Malnutrition and severe food insecurity are on the rise in sub-Saharan Africa. Cowpea (Vigna unguiculata L.), an indigenous plant from Africa with a good nutritional composition, can be a strategic tool in the fight against hunger. Hence, the objective of this study was to assess the yield response of different cowpea accessions to soil amendments. The study adopted a 5 × 4 factorial in a randomized complete block design with three replications. The factors comprise five cowpea accessions (BBL, BBR, BCB, EBL and EBC) and four soil amendments (poultry manure [PoM], pig manure [PgM], NPK 15:15:15 fertilizer and control). There are significant differences among the cowpea accessions in all the studied attributes. The stability and mean performance analyses revealed that the top-ranked accessions were EBL and EBC, while BBL, BBR and BCB were below the population mean. The ranking order of the soil amendments was PoM > PgM > population mean > NPK > control. Accession EBL amended with PoM gave the highest plant weight (106.4 g), which was statistically similar to the same accessions amended with NPK (104.9 g) and PgM (100.4 g), but significantly higher than the other treatment combinations. Plant weight has a significant and positive correlation with pod length (r = 0.919**), number of leaves (0.623**), vine length (0.361**) and hundred seed weight (0.329*). The findings of this study showed that cowpea accessions responded differently to the soil amendments. This study recommends the use of additional nutrients as a supplement in the production of cowpea rather than relying solely on its self-fixed nitrogen.